Milk Products Diversification to Increase Profit of Dairy Goat Farming - Sumanto . (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2016)
Dairy goat farming in Indonesia is growing because goat milk is attractive as nutrient supplement and alternative medicine for human health. Selling fresh goat's milk often becomes a constraint because not all consumers can drink it due to unpleasant smell. Effort on diversification of fresh goat's milk into processed milk products is considered a good option, but only few farmers have done it. Milk processing is useful to eliminate the smell of fresh goat's milk and to increase value-added. Goat population is around 19.01 million head, while dairy goat population has not been known yet. The paper describes the benefit of processing  fresh goat milk to increase goat farming profit through the improvement of feed management, and selling the processed milk. Better management increase lactation period from 170 to 250 days, milk production from <1 to 2 liter/head/day, and higher price of processed milk. Investment on 59 does and 7 bucks for five years through the goat milk diversification has increased profit by 33.53%. Diversification of processing goat milk product is necessary to increase productivity and value added of fresh milk.